Primary School Teacher’s Perception of Game-Based Learning in Online Learning: The Advantages and Challenges - Siburian, Sri Nani Rezeki; Mahmud, Yogi Saputra (Universitas Muhammadiyah Mataram, 2022)
The COVID-19 pandemic has impacted almost all aspects of life, including education. This unprecedented shift to online learning has forced schools to implement distance learning through online-based learning. To keep the students engaged and motivated through online learning, many teachers changed their learning method from traditional learning to game-based learning (GBL) by incorporating games into learning. This study investigated primary school teachers' perceptions of game-based learning advantages and challenges in Science Learning on online learning during the COVID-19 pandemic. The data were collected through observation and semi-structured interviews of five primary school teachers and analyzed using thematic analysis of qualitative data. The results revealed that the teachers found a positive association between GBL and students' performance. GBL is a learning media that could engage students' participation and learning motivation in class. However, some teachers were also concerned about the declines in students' grades and several obstacles teachers encountered while implementing GBL. Some recommendations for future research and practice are proposed in the current study.